PELATIHAN KOMPUTER UNTUK PENINGKATAN KOMPETENSI GURU MTS DARUS SAADAH PEDURUNGAN - Atiyah Salwa; Muhamad Sidik; Ratna Ayu Pawestri Kusuma Dewi; Angelina Kurnia Juita (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
The progress of science and technology of a nation is certainly inseparable from the success of the learning process in higher education institutions and institutions in that country. The stages of change are expected to be able to bring the nation towards the progress of a higher civilization and permeate as a whole as the identity of the nation. The level of mastery of science and technology is clear evidence of the success of development. Improving mastery of science and technology is not only carried out in formal education, but can also be carried out through non-formal education. Information technology has developed very rapidly and covers various fields. The field of education is one of the fields that is influenced by information technology, both in the formal learning process at school and non-formal in the form of training outside of school